Investigation on nozzle throat erosion in hybrid rocket motor due to nozzle expansion ratio - Mohd Ali, Mohd Aizat Iz’aan; Razali, Muhammad Farhan; Azami, Muhammad Hanafi; Abdul Hamid, Ahmad Hussein (Aerospace Society Malaysia, 2023)
Rocket nozzle is one of the core elements in rocket motors. Throughout the years, nozzle throat erosion in rocket motors has been heavily discussed by researchers, especially in the hybrid rocket motor due to a high amount of oxygen and unburned propellant in the combustion product. Generally, throat erosion occurs in the rocket nozzle throat where the flow experiences minimum area due to the dissipation of its material. The velocity of the hot gas in the nozzle increases throughout the converging-diverging section of the nozzle and such high speed at the throat area causes the throat erosion, which leads to enlarged nozzle throat area that consequently causes reduction in the motor performance. The purpose of studying the nozzle throat erosion is to have a closer reach to understanding of the nozzle throat erosion factors, behaviors and effects towards the efficiency of rocket propulsion. In this study, the primary focus is on the effects of the nozzle expansion ratio to the throat nozzle erosion. Based on the simulation results in ANSYS and theoretical calculations, it is found that the thrust decreases as the expansion ratio increases. Therefore, it is concluded that rate of nozzle erosion increases as expansion ratio increases, which is shown to be caused by high-speed velocity of the firing going through the small area of the nozzle throat.